Distributed Maximum Power Tracking for High Performance Vehicle Solar Arrays - Wolfs, Peter; Tang, L.; Senini, S. (University of Queensland, 2004)
Recent advances in low voltage electronics make possible the development of maximum power tracking converters for single high performance solar cells. Application areas include vehicle arrays where curvature of the array may be significant or where dappled lighting by roadside vegetation or structures produces highly irregular and rapidly changing illumination. This paper will present a design for a high efficiency 600mW maximum power tracking converter for a single dual junction germanium gallium arsenide cell. Switching frequency and synchronisation guidelines for arrays of tens to hundreds of cells with individual cell power tracking are presented.